Trade of Debts Resulting from Financial Intermediation: Analysis from Sharia Perspective - Abdulazeem Abozaid (Justicia Islamica, 2022)
The modern financial system encourages people to incur debts to fulfill basic needs and spend beyond one’s wants. The core of this system is based on interest, which results from the financial intermediation between creditors and borrowers. Regardless of the interest element prohibited in Islam, the notion of excessive debt creation through financial intermediation and trading the debt is very serious, as it may lead to global financial crises. The study seeks to address debt trading from a Sharia perspective and address the justifications and attempts by some institutions to validate debt trading despite its established prohibition in Sharia. To achieve the above, the paper employs qualitative research methodology, which adopts a textual analysis approach together with a review of the stands of the contemporary Fiqh bodies. The study finds that the excessive creation of debt through financial intermediation and its concentration in financial institutions poses a severe threat to the economy and carries the seeds of financial crises. Following debt creation and concentration, debt trading aggravates the situation. It pushes it beyond borders, whereas Sharia, through prohibiting debt trading, advocated thoroughly in the study, gives Islamic finance genuine immunity against financial crises.